Structural characterization of subunit b of the bacterial F1FO ATP synthase and the critical roles of conserved P-loop residues of the archaea A1AO ATP synthase subunit A - Ragunathan Priya (2011)
Adenosine 5’-triphosphate (ATP) synthesis by oxidative phosphorylation or photophosphorylation is a multistep membrane-located process that provides the bulk of cellular energy in eukaryotes and many prokaryotes. The majority of ATP synthesis is accomplished by the enzyme ATP synthase (EC 3.6.1.34) also called as F1FO ATP synthase, which, in its simplest form, as in bacteria, is composed of eight different subunits. This multi-subunit complex is divided into the F1 headpiece, α3:β3, attached by a central and a peripheral stalk to a membrane-embedded ion-translocating part known as FO. The central stalk is made up of γ and ε and the peripheral stalk consists of b and δ. As the central stalk is driven by the passage of protons through a pore formed by the c and a subunits of FO, the rotation of γ within α3β3 of F1 causes conformational changes in the catalytic nucleotide binding sites in β-subunits, resulting in ATP synthesis and release. One main function of the b2δ stator is to hold the α3β3 hexamer against the rotational torque caused by the rotation of the central stalk. The b subunit dimer in the peripheral stator stalk of Escherichia coli ATP synthase is essential for enzyme assembly and the rotational catalytic mechanism.